Inflammatory Myofibroblastic Tumor Arising in the Pancreatic Head: a Rare Case Report - Panda, Devasis (Indian J Surg, 2015)
Inflammatory myofibroblastic tumor (IMT) is a rare neoplastic lesion with tendency toward local aggressive behavior and recurrence. It is primarily a visceral and soft tissue tumor; however, involvement of pancreas is extremely unusual. A localization in the pancreas needs differentiation from other tumors and chronic pancreatitis. We report a case of inflammatory myofibroblastic tumor arising in pancreatic head in a 32-year-old female who underwent Whipple’s procedure.